Case Report: Evaluation of Patient Diagnosed Perianal Fistula According to Abdellah's 21 Nursing Problems Model - Ilknur Yücel; M. Nasrullah ER (KHD Production, 2023)
This case report aimed to provide nursing care to the patient diagnosed with Perianal Fistula for the nursing diagnoses in Faye Abdellah's